Peran Bimbingan dan Konseling Islam dalam Mengatasi Rendahnya Kepercayaan Diri Siswa MTS dalam Interaksi Teman Sebaya - Nuri Handayani Siregar; Siti Harahap; Zunnu Wanis Alfarisi; Naila Alzahwa; Ramadan Lubis (STKIP Subang, 2026)
Self-confidence is an important aspect of adolescents’ social development that influences their ability to interact and adapt to their environment. Students with low self-confidence tend to experience difficulties in communicating and forming relationships with their peers. This study aims to examine the forms of low self-confidence among MTs students in peer interactions, the factors that influence it, and the role of Islamic Guidance and Counseling in helping to address these issues. The study employed a qualitative approach using a case study design. The participant was a seventh-grade student at the UINSU Medan Laboratory MTs, selected through purposive sampling. Data were collected through observation, semi-structured interviews, and field notes, and were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that low self-confidence is characterized by difficulty initiating conversations, speaking in a soft voice, feeling shy when interacting with unfamiliar peers, and a tendency to limit social interactions to close friends. Influencing factors include internal factors such as fear, shyness, and self-doubt, as well as external factors such as the social environment and the need for acceptance by peers. Islamic Guidance and Counseling plays a role through individual counseling, group counseling, motivation, and spiritual approaches to help boost students’ self-confidence in social interactions.